(untitled) (Global Journal of Human-Social Science, 2024)
This paper explores the role of informal cross-border trade ICBT along the Eritrean-Ethiopian borderlands amidst a situation of war and uncertainty It seeks to understand whether ICBT has contributed to the socio-economic recovery of people living on either side of the border and to rebuilding peace It draws on semi-structured interviews and focus group discussions conducted with local informants between May and November 2021 including smugglers traders local officials border guards and ordinary inhabitants of Serha and Senafe as well as my previous fieldwork and personal experiences in Eritrea and Ethiopia My findings reveal that despite some challenges ICBT has the potential not only to mitigate socioeconomic problems among war-torn borderland communities but also to enhance cross-border relations by breaking down the stereotypes of suspicion and mistrust concocted by the warring states